Construção e evidências de fidedignidade e validade de uma escala de leitura e escrita (ELE) para o rastreio de crianças com dificuldades escolares - Moraes, Ana Bassôa de (2016)
Objectives: To develop and collect evidence of validity and reliability for a screening scale for reading and writing skills for children. Methods: 1) review of the literature; 2) evaluation by experts; 3) evaluation by teachers; 4) application of the instrument with 95 students and evaluation of the students with standard reading and writing tests. Data Analysis: We carried out factor analysis, Cronbach alpha r, Rash model, item response theory, Spearman correlation between scale scores and the reading and writing tasks, test-retest reliability coefficient. Results: the main results were (1) development of a 16-item Likert scale for 16 symptoms for reading and writing difficulties; (2) presence of one factor and high factor loads in the factor analysis of the scale; (3) strong internal consistency for the alpha r (0.968), and the item response theory showed greater precision in the evaluation of children with average or low performance; (4) moderate Spearman correlation for 11 of the 16 external variables; (5) temporal stability showed correlation of 0.80. Conclusion: The study shows evidence of validity and reliability for the scale, which indicates the scale is a reliable instrument for teachers and healthcare professionals involved with pediatric patients and interested in investigating language skills.